A is for alibi eaudiobook - Grafton, Sue (Kinsey Millhone, 2005)
Now Available on CD! 3 CDs/ 3 hours Read by Judy Kaye Plenty of people in the picturesque town of Santa Teresa, California, wanted Laurence Fife, a ruthless divorce attorney, dead.  Including, thought the cops, his young and beautiful wife, who was convicted of the crime. Now, eight years later and out on parole, Nikki Fife hires Kinsey Millhone to find out who really killer her husband.  Kinsey must pursue a trail that's eight years old: one that leads from a young boy, born deaf, whose memory cannot be trusted; to a lawyer defensively loyal to his dead partner - and disarmingly attractive to Millhone; to a not-so-young secretary with too high a salary for far too few skills. This train will twist to include them all, with Kinsey following every turn until it finally twists back on itself and she fins herself face-to-face with a killer cunning enough to get away with murder.